Youth in digital culture and media: global and Scandinavian perspectives - Carlsson , Ulla (Anàlisi, 2013)
This article addresses the current challenge to empower young people in the use of media (internet, mobile phone, use of the new possibilities such as social networks) through media literacy so that it enable them to be conscious actors in this new media landscape that has changed everything, including the type of relationship that children and young people establish with the media.After a review of studies that show where and how young people use the new media in the Nordic countries, and to retrieve data that show how the new digital gap is just a new manifestation of the inequalities between rich and poor countries that already existed, the author makes an urgent call to all those involved —politicians, Internet content providers, media industry, school, scientific community, parents, young people themselves, etc. - to participate in the development of conditions that maximize the potential of new technologies information and minimize the risks involved.